Macroprudential Policies to Enhance Financial Stability in the Caucasus and Central Asia - Khandelwal, Padamja; Al-Farah, Rayah; Cabezon, Ezequiel; Mirzayev, Sanan (Washington, D.C. : International Monetary Fund, 2022)
Limited economic diversification has made the economies of the Caucasus and Central Asia particularly vulnerable to external shocks. The economies in the region are heavily reliant on oil and mining exports as well as remittances. In some countries, tourism and capital flows also play a prominent role in aggregate economic activity.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Banks; Depository Institutions; Financial Crises; Financial Institutions and Services; Micro Finance Institutions